Integration between the strategies of negotiation and conflict management strategies A prospective study in a sample of business organizations, the Iraqi - عبد الرضا فرج بدراوي; ahlam of Ali Hamad Al-Najafy (Iraqi Journal for Administrative Sciences, 2024)
The study aims to emphasis the integration between negotiation and the effectives of conflict administration strategies within the working environment of Iraqi business organization. The Iraqi society has its own merits which require great efforts to ever come problems such as bias, un compromising opines and introducing personal stands in any decisions making process. A constructive dialog based on a common interest is suggested in this study by introducing several scenarios to achieve understanding and coordination in any negotiating process. Conflicts have been dealt with and employed to serve common coals. Background theories have been analysis used and related to the field surveys. Therefore a questionnaire was designed and the data were collected and statistically analyzed. The study also employs some basic assumptions which have an influence and morale relationship will both negotiation and conflict strategies the field survey included (125) persons represent (6) organizations. Finally it is concluded that it is important to establish integration between competitive strategies and conflict administration.